Ocular Side Effects of Sildenafil That Persist Beyond 24 h—A Case Series - Karaarslan, Cüneyt (Frontiers in Neurology, 2020)
Acute secondary effects of sildenafil, a first-line pharmacotherapy for erectile dysfunction (ED), include headache, heartburn, skin flush, and vision changes. Generally, these effects subside within 5 hours. This is a retrospective report of 17 cases in which patients experienced visual disturbances following 100-mg sildenafil use that persisted for more than 24 hours. All 17 patients were healthy men taking sildenafil for the first time without prescriptions who sought consultation at our clinic within 48 hours of taking the drug. Diagnostic tests indicated that out of the 17 patients, nine had photophobia, 13 had disrupted color perception, nine had impaired visual acuity, three had deficiencies in stereopsis, six had disrupted contrast sensitivity, and eight had abnormally dilated pupils. These disturbances resolved within 21 days in all 17 cases. There was near-full case overlap between photophobia and color vision impairment. In conclusion, because some individuals have heightened sensitivity to sildenafil, perhaps due to metabolic variance, patients should be started on a modest trial dose.